2021
DOI: 10.1021/acschemneuro.0c00723
|View full text |Cite
|
Sign up to set email alerts
|

Programmable DNA Nanodevices for Applications in Neuroscience

Abstract: The broad area of neuroscience has witnessed an increasing exploitation of a variety of synthetic biomaterials with controlled nanosized features. Different bionanomaterials offer very peculiar physicochemical and biochemcial properties contributing to the development of novel imaging devices toward imaging the brain, or as smartly functionalized scaffolds, or diverse tools contributing toward a better understanding of nervous tissue and its functions. DNA nanotechnology-based devices and scaffolds have emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 169 publications
0
16
0
Order By: Relevance
“…10,11,14 DNA hydrogels are a programmable selfassembled network of multiple DNA strands. 15 We previously demonstrated that DNA hydrogels act as a cushion for cell attachment, cell growth, and cell spreading. Additionally, the adhesive properties of DNA hydrogels reprogramme the cellular membrane for enhanced receptor expression and endocytosis mechanisms.…”
Section: Dhiraj Bhatiamentioning
confidence: 99%
“…10,11,14 DNA hydrogels are a programmable selfassembled network of multiple DNA strands. 15 We previously demonstrated that DNA hydrogels act as a cushion for cell attachment, cell growth, and cell spreading. Additionally, the adhesive properties of DNA hydrogels reprogramme the cellular membrane for enhanced receptor expression and endocytosis mechanisms.…”
Section: Dhiraj Bhatiamentioning
confidence: 99%
“…[58][59][60] Exploring synthetic biology and materials science in relation to neural recording and stimulation also offers unique and promising perspectives. 52,61 Additionally, various advances in micro-and nano-structured materials highlight the expanding frontiers of this field and the vast potential of leveraging machine intelligence and semiconductor technology. 62 In the following subsections, we focus on nanomaterialbased bioelectrical interfaces with applications in the nervous system.…”
Section: Nervous Systemmentioning
confidence: 99%
“…DNA nanotechnology-based devices and scaffolds as materials have been used for cell and tissue engineering. 61 These materials are promising because they are biocompatible and highly adaptable in biological systems and do not induce strong negative immune responses.…”
Section: Outlook and Future Directionsmentioning
confidence: 99%
“…DNA nanostructures typically exhibit enhanced stability, biocompatibility, cellular permeability, low cellular toxicity, and high resistance to enzymatic degradation, making them suitable for both in vitro and in vivo applications. , DNA nanostructures with well-defined geometries in sizes can be delivered to specific cells by triggering chemical, molecular, and environmental signals to release targeted molecules and offer tunable cellular uptake profiles. DNA nanocarriers like nanocages have been used for cellular and in vivo delivery of different types of cargo molecules such as small molecules, peptides, antibodies, and oligonucleotides. Many unmodified DNA nanodevices cannot be internalized efficiently in cells without any transfection agent because of the polyanionic nature of DNA molecules. However, few devices of small size and specific geometry have been shown to be internalized into cells and in vivo . , Three-dimensional DNA nanocages like tetrahedral DNA nanocages (TDN) and icosahedral DNA nanocages (IDNs) can enter different cell types without any aid of a transfection agent.…”
Section: Introductionmentioning
confidence: 99%